2020
DOI: 10.1016/j.concog.2020.102902
|View full text |Cite
|
Sign up to set email alerts
|

Forcing you to experience wonder: Unconsciously biasing people’s choice through strategic physical positioning

Abstract: Magicians have developed powerful tools to covertly force a spectator to choose a specific card. We investigate the physical location force, in which four cards (from left to right: 1-2-3-4) are placed face-down on the table in a line, after which participants are asked to push out one card. The force is thought to rely on a behavioural bias in that people are more likely to choose the third card from their left. Participants felt that their choice was extremely free, yet 60% selected the 3rd card. There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Furthermore, some magic tricks force the spectators to choose a certain object while the spectators believe that they made the choice out of their free will. Investigating how and why spectators have such false beliefs can lead to better understanding of human free will and agency (Kuhn, Pailhès, & Lan, 2020;Olson, Amlani, & Rensink, 2013;Ozono, 2017;. Our magic trick videos include misdirection, illusion, and forcing as well as other various trick mechanisms (e.g., tricks utilizing mathematical logic or physical principles), allowing researchers to pursue a variety of psychological research questions.…”
mentioning
confidence: 99%
“…Furthermore, some magic tricks force the spectators to choose a certain object while the spectators believe that they made the choice out of their free will. Investigating how and why spectators have such false beliefs can lead to better understanding of human free will and agency (Kuhn, Pailhès, & Lan, 2020;Olson, Amlani, & Rensink, 2013;Ozono, 2017;. Our magic trick videos include misdirection, illusion, and forcing as well as other various trick mechanisms (e.g., tricks utilizing mathematical logic or physical principles), allowing researchers to pursue a variety of psychological research questions.…”
mentioning
confidence: 99%
“…Other authors have already described a positional bias influencing choice using everyday objects, but in this case, the selected position is the first, not the second, from the right (Nisbett & Wilson, 1977). Kuhn, Pailhès & Yuxuan (2020), suggest that this preference for the second position is caused by a similar positional bias towards the card that it is easiest to reach from the point of view of the spectator. However, in magic shows, sometimes the magician deals the cards on the table at a slant, if the positional bias was the only responsible for people's choices, the selected card in this case would be the one closest to the spectator, that is, the first one from the right.…”
Section: Intuitive Decisions (Forces Manipulating Decisions)mentioning
confidence: 61%
“…These results were truly unexpected and confirm that magicians do not always know why their tricks work. Our previous research ( Kuhn et al, 2020 ) has shown that magicians are good at estimating the effectiveness of a force, but their intuitions about its mechanism are not necessarily correct. A more scientific approach to the art of magic can illustrate why their tricks work, which in turn might help them develop more refined and more powerful deceptive principles ( Kuhn, 2019 ; Rensink & Kuhn, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Let us now take a closer look at these two types of forces. Choice forces refer to techniques in which the magician covertly influences a person’s choice, and several of these techniques have been empirically investigated ( Kuhn et al, 2020 ). Shalom and colleagues studied the “Classic Force,” which involves asking a spectator to choose a card by physically picking it.…”
Section: Introductionmentioning
confidence: 99%